If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 + -3 = 2 Reorder the terms: 5 + -3 + 6x = 2 Combine like terms: 5 + -3 = 2 2 + 6x = 2 Add '-2' to each side of the equation. 2 + -2 + 6x = 2 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 2 + -2 6x = 2 + -2 Combine like terms: 2 + -2 = 0 6x = 0 Solving 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 0 Simplifying x = 0
| -2(t-1)+5t=7t-5 | | 4x+6x-16=3x+2x-26 | | 5x+y=62 | | 4(y-4)/5=-3y | | 6(6x-5)-5=36x-35 | | 0.04(y-4)+0.18y=0.02y-0.05(10) | | d(q-9)= | | 0.70x+0.35(100)=0.35(64) | | 0.50x+0.25(110)=0.25(40) | | 100*x=1.9247 | | -3(y-1)+2=4(y-3) | | z.16/2 | | -4-27=6y+13 | | x-2/3x | | 3.9(2x-1)+3.9x= | | -1.6(-3m+8)+2.3m= | | 2x+8x-4=x+768 | | 4-4y=9-5y | | r-2/3r | | 7x+2x+30=x+270 | | 8-(-3.4+6.45)= | | 8c+100=-12 | | 11-4x=(3x-2)(3x-2)+1 | | 7(x-2)+8=7x+3 | | (9f/2g)(4) | | -24=6+5w | | 50-3a=122 | | 12+8w=76 | | 36b^2-121= | | 4(5y-2)+3(2y+6)=25(3y+2)-19 | | 2v^2-20v+48= | | -2g=3.28 |